CRISPR/Cas9 ribonucleoprotein-mediated genome and epigenome editing in mammalian cells - Bloomer, Hanan; Khirallah, Jennifer; Li, Yamin; Xu, Qiaobing (Advanced drug delivery reviews, 2022)
[Display omitted] The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) system has revolutionized the ability to edit the mammalian genome, providing a platform for the correction of pathogenic mutations and further investigation into gene function. CRISPR reagents can be delivered into the cell as DNA, RNA, or pre-formed ribonucleoproteins (RNPs). RNPs offer numerous advantages over other delivery approaches due to their ability to rapidly target genomic sites and quickly degrade thereafter. Here, we review the production steps and delivery methods for Cas9 RNPs. Additionally, we discuss how RNPs enhance genome and epigenome editing efficiencies, reduce off-target editing activity, and minimize cellular toxicity in clinically relevant mammalian cell types. We include details on a broad range of editing approaches, including novel base and prime editing techniques. Finally, we summarize key challenges for the use of RNPs, and propose future perspectives on the field.